2022
DOI: 10.1002/mnfr.202100950
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Fat High‐Fructose Diet Dysregulates the Homeostatic Crosstalk Between Gut Microbiome, Metabolome, and Immunity in an Experimental Model of Obesity

Abstract: Scope Ample evidence supports the prominent role of gut‐liver axis in perpetuating pathological networks of high‐fat high‐fructose (HFF) diet induced metabolic disorders, however, the molecular mechanisms are still not fully understood. Herein, this study aims to present a holistic delineation and scientific explanation for the crosstalk between the gut and liver, including the potential mediators involved in orchestrating the metabolic and immune systems. Methods and Results An experimental obesity‐associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 71 publications
0
12
1
Order By: Relevance
“…As shown in Figure 5 A, SFN treatment significantly reduced the LPS level in the liver. The ability to recognize the increased LPS, TLR4 and their downstream pathway has shown dominance in the mechanisms of the microbiota-gut-liver axis [ 42 ]. LPS is a key factor in inducing an inflammatory response in liver tissue and plays an important role in liver injury through the LPS-TLR4 signaling pathway [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5 A, SFN treatment significantly reduced the LPS level in the liver. The ability to recognize the increased LPS, TLR4 and their downstream pathway has shown dominance in the mechanisms of the microbiota-gut-liver axis [ 42 ]. LPS is a key factor in inducing an inflammatory response in liver tissue and plays an important role in liver injury through the LPS-TLR4 signaling pathway [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on animals and humans have reported altered gut microbes in NAFLD individuals. Gut microbiota dysbiosis was observed in HFHFr-induced obese rats [ 42 ]. We observed that SFN decreased the F/B ratio and the abundance of Lactobacillus , Lactococcus , Blautia , Dubosiella , and Alistipes at the phylum level in HFHFr mice.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal contents contain nonabsorbable food components and complex mixtures of metabolites produced by the host and intestinal microbes. 24 Therefore, intestinal metabolites can reflect the health status of the host. Based on this, we examined the intestinal metabolome of obesity model mice, which consists of a mixture of host-produced and microbiota-produced molecules.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Seq was performed as described previously before [ 67 ]. Briefly, total RNA for hepatic transcriptome sequencing was isolated and purified using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) following the manufacturer’s procedure.…”
Section: Methodsmentioning
confidence: 99%